Learning and Instruction in the Digital Age - Spector, J. Michael.; Ifenthaler, Dirk.; Isaias, Pedro.; Kinshuk.; Sampson, Demetrios. (Springer US, 2010)
Instruction tailored to the individual student, learning and teaching outside the limits of time and spaceideas that were once considered science fiction are now educational reality, with the prospect of an intelligent Web 3.0 not far distant. Alongside these innovations exists an emerging set of critical-thinking challenges, as Internet users create content and learners (and teachers) take increased responsibility in their work. Learning and Instruction in the Digital Age nimbly balances the technological and pedagogical aspects of these rapid changes, gathering papers from noted researchers on a wealth of topics relating to cognitive approaches to learning and teaching, mental models, online learning, communications, and innovative educational technologies, among them: Cognition and student-centered, Web-based learning The progression of mental models throughout a course of instruction Experiencing education with 3D virtual worlds Expanding educational boundaries through multi-school collaboration Adapting e-learning to different learning styles The student blog as reflective diary With its blend of timely ideas and forward thinking, Learning and Instruction in the Digital Age will enrich the work of researchers in educational psychology, educational technology, and cognitive science.